Pembuatan Cetakan Pasir Dan Proses Pemesinan Untuk Komponen Blok Pompa Pada Mesin Pompa Air Merk Matrix Model Mtx-22c - Firdaus Firdaus; Rakiman Rakiman; Nota Effiandi; Yuli Yetri (Politeknik Negeri Padang, 2018)
Reverse Engineering (RE) is a process in manufacturing that aims to reproduce or recreate existing models, either components, sub-components, or products without using existing design documents or working drawings. Through this reverse engineering idea, the process of making the Pump Block component is started with making part and mold design, making sand casting, then finished with machining processes. The machining process that is carried out is the turning process, the milling process, and the drilling process which is assisted by using jigs and fixture to make it easier on finishing the Pump Block parts in the machining process. By using the processes, so it is produced the similar pump block that is resemble with desired original object.